Dear substitute - Scanlon, Elizabeth Garton; Vernick, Audrey (Disney/HYPERION, 2018)
In a series of letters a student laments the absence of her teacher and daily routine, but she soon realizes there are benefits to mixing things up, and that perhaps having a substitue teacher is not so bad afterall.